PENGARUH RESIDU BIOCHAR KOTORAN AYAM DIPERKAYA AMONIUM SULFAT TERHADAP SIFAT KIMIA TANAH, SERAPAN N DAN PRODUKSI TANAMAN PADI PADA TANAH DENGAN TEKSTUR BERBEDA - Megawati Ompusungu; Yulia Nuraini (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Soil texture is one of the determinants of soil fertility. One of the efforts in overcoming the problems of soil is by biochar. The purpose of this study was to determine the ammonium sulphate enriched biochar residues on several soil chemical properties, N uptake, and rice yield on soils with different texture. This study that was conducted at experimental farm of Tribhuwana Tunggadewi University used a randomized complete block design with two factors, i.e.biochar and soil texture. Biochar factor consisted of zero biochar (T), chicken manure biochar (BK), and ammonium sulphate enriched biochar (BA). Soil texture factor consisted of sandy silt texture (P), silt (D), and clay (L). Parameters observed were soil chemical properties (organic matter, pH, CEC, total N total), N uptake by rice, rice plant height, rice panicle, productive tillers, grain dry weight, dried grain. Results of the study showed that ammonium sulphate enriched biochar residue affected the pH and N total soil in different textures, ie on clay texture, silt then sandy silt with values 6,39 ; 6,37; 6,13 and 0,08 %; 0,10 %; 0,09 %. Soil texture affected N uptake on clay texture, silt then sandy silt with value 15,97 g plant-1 ; 12,88 g plant-1; 7,42 g plant-1. Significant effects on plant’s height, productive tillers, dry weight of grain and dried grain to biochar factor, the ammonium sulphate enriched biochar had highest value 106,17 cm; 6.22 polybags-1; 12,74 g; 9,40 g.